firebird
If f(x) = xsquared does f(a+1) = (a+1)squared



This Question is Closed

ASAAD123
Best Response
You've already chosen the best response.
0
what's the question?

firebird
Best Response
You've already chosen the best response.
0
if f(x) = X squared does it follow that f(a+1) = (a+1) squared

mark_o.
Best Response
You've already chosen the best response.
0
True :D

ASAAD123
Best Response
You've already chosen the best response.
0
yes

firebird
Best Response
You've already chosen the best response.
0
explain why

ASAAD123
Best Response
You've already chosen the best response.
0
replace x with (a+1).

firebird
Best Response
You've already chosen the best response.
0
How do you evaluate the expresssion f(g(4)) when f(x)= 3x and g(x)= x2

ASAAD123
Best Response
You've already chosen the best response.
0
f(g(4))=3(42)=6

hba
Best Response
You've already chosen the best response.
2
@firebird Do you understand ?

firebird
Best Response
You've already chosen the best response.
0
no

hba
Best Response
You've already chosen the best response.
2
So let me explain that to you
We have to find f(g(4)
So we have to find
g(4) first
g(x)=x2
then
g(4)=

Shadowys
Best Response
You've already chosen the best response.
0
note:
if f(x)=3x, g(x)=x2,
then f(g(x))=3(g(x))=3(x2)

ASAAD123
Best Response
You've already chosen the best response.
0
f(g(x)) :substitute g(x) in x of f(x).

Shadowys
Best Response
You've already chosen the best response.
0
simply sub anything inside x as long it's in the domain.

hba
Best Response
You've already chosen the best response.
2
@firebird Do you follow me ?

firebird
Best Response
You've already chosen the best response.
0
yes

hba
Best Response
You've already chosen the best response.
2
So what did you get ?
g(4)=

firebird
Best Response
You've already chosen the best response.
0
42=g(x)

firebird
Best Response
You've already chosen the best response.
0
So under the same values of f(x) and g(x), g(f(4)) is equal to g(3(x)) which is equal to
x2(3x)?